A Successful Fertility Outcome after Assisted Reproduction in a Woman with Endometrial Hyperplasia without Atypia Following Progesterone Therapy - Raguraman, S.; Muhunthan, K. (South Asian Federation of Obstetrics and Gynaecology, 2022)
Aim: The aim of the case report is to demonstrate a case of successful assisted reproductive technology treatment in a woman with endometrial hyperplasia without atypia. Background: Endometrial hyperplasia (EH) is a premalignant lesion of endometrial carcinoma, and its incidence is three times higher than endometrial carcinoma. The impact of endometrial hyperplasia on fertility and advanced fertility treatments is not clear. However, the regression of endometrial hyperplasia without atypia following progesterone therapy has shown favorable fertility outcomes and is recommended before advanced fertility treatment. Case description: A 41-year-old woman with a history of subfertility for 11 years and a history of heavy menstrual bleeding for 3 years, presented for assisted reproductive technologies (ART) treatment. Owing to heavy menstrual bleeding and persistently high endometrial thickness, she underwent a hysteroscopic assessment and endometrial sampling, which revealed endometrial hyperplasia without atypia. She was treated with six cycles of continuous oral progesterone and a repeat endometrial sampling after six months which revealed secretory endometrium. She underwent transfer of two embryos and had a singleton gestation. She had a successful pregnancy with an uneventful antenatal period and delivered a 2800 gm baby by elective cesarean section. Conclusion: Disease regression should be achieved before starting fertility treatment and ART treatment is more successful compared with natural conception in a patient with endometrial hyperplasia. Clinical significance: Even though there is no robust evidence to suggest endometrial hyperplasia without atypia has a negative impact on ART, free radical generation, and oxidative stress reactions shown in the pathogenesis of endometrial hyperplasia might negatively impact ART. Successful fertility treatment is possible after successful treatment of endometrial hyperplasia.
Keywords: Assisted reproduction; Endometrial hyperplasia without atypia; Progesterone therapy